Real-time encoding and compression of neuronal spikes by metal-oxide memristors - Isha Gupta (Nature Portfolio, 2016)
The need for intelligent compression of big data, for example in neuroscience, has sparked interest in neuromorphic data processing. Here, Gupta et al.use memristors as event integrators to encode and compress neuronal spiking activity recorded by multi-electrode arrays.